Mangrove soil-derived Streptomyces: an important resource of pharmaceutical active natural products - Xuefeng ZHOU (KeAi Communications Co., Ltd., 2022)
The mangrove soil-derived microbes, especially genus Streptomyces strains, have proven to be a rich source of bioactive secondary metabolites and play a critical role in the development of pharmaceutical researches. To understand the structural diversity and bioactivities of the metabolites from the mangrove soil-derived Streptomyces strains, this review for the first time provides a comprehensive overview of 168 natural products isolated from the mangrove soil-derived Streptomyces strains with their bioactivities, up to the end of 2021. Most of the structural types of these compounds are alkaloids, lactones, xanthones, and quinones. The pharmacological mechanisms of some representative lead compounds are well studied, revealing that they have important medicinal potential. This review provides an important reference for the research status of natural products isolated from mangrove soil-derived genus Streptomyces, and reveals that mangrove soil-derived Streptomyces is an important resource of pharmaceutical molecules.